International and Inregional Premises of Formation of the Labor Market in Russia - KHAIRULLINA, Nursafa Gafurovna; GAISINA, Lyutsiya Mugtabarovna; KRASULINA, Natalia Alexandrovna; BEREZHNOVA, Zulfiya Zifovna; GREB, Andrey Vladimirovich (Journal of Advanced Research in Law and Economics; Vol 6 No 1 (2015): JARLE Volume VI Issue 1(11) Summer 2015, 2016)
The article presents the results of a secondary analysis of the results of public preferences research on social problems of migrants, which arrive to the region from the countries of Central Asia, on the basis of a questionnaire survey of 1200 respondents living in the Tyumen region, and also experts’ opinions. Statistic data, which characterize processes of arrival and departure of foreign citizens, has been analyzed. Results of questionnaire of social opinion gave a chance to conclude, that the situation in the area of labor migration is more pleasant, than the results of social opinion about migrants in Russia in general.
Keywords: migration, migrants, migration processes, social problems, interethnic relations